SRSF3 Promotes Angiogenesis in Colorectal Cancer by Splicing SRF - Chen, Yinshuang; Yang, Man; Meng, Fanyi; Zhang, Yawen; Wang, Mengmeng; Guo, Xuqin; Yang, Jie; Zhang, Hongjian; Zhang, Haiyang; Sun, Jing; Wang, Weipeng (Frontiers in Oncology, 2022)
SRSF3, an important member of the serine/arginine-rich protein (SRp) family, is highly expressed in various tumors and plays an important role in tumor cell proliferation, migration and invasion. However, it is still unclear whether SRSF3 is involved in tumor angiogenesis. In this study, we first revealed that SRSF3 regulated the expression of numerous genes related to angiogenesis, including proangiogenic SRF. Then, we confirmed that SRSF3 was highly expressed in colorectal cancer (CRC) and was positively correlated with SRF. Mechanistic studies revealed that SRSF3 directly bound to the “CAUC” motif in exon 6 of SRF and induced the exclusion of introns. Knockdown of SRSF3 significantly reduced the secretion of VEGF from CRC cells. Conditioned medium from SRSF3-knockdown CRC cells significantly inhibited the migration, invasion and tube formation of human umbilical vein endothelial cells (HUVECs). In addition, SRF silencing inhibited angiogenesis, while SRF overexpression reversed the antiangiogenic effects of SRSF3 knockdown on tube formation. These findings indicate that SRSF3 is involved in the splicing of SRF and thereby regulates the angiogenesis of CRC, which offers novel insight into antiangiogenic therapy in CRC.